Zasady funkcjonowania islamskiego systemu finansowego - Mirecka, Elżbieta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The complexity of islamic banking results from the combination of the mode of its functioning within the islamic code and the disapproval of modern banking. The employment of financial capital Interest free and the return to traditional financing methods in the form of mudaraba and musharaka art confronted with difficulties whose causes are to be found in the absence of an islamic financial market and little involvement of monetary authorites of Islamic countries. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 214-223